Implikasi Pasal 32 ayat (2) dan (3) Undang-Undang Nomor 1 Tahun 2011 terhadap Pemenuhan Standar Nasional Indonesia (SNI) Terkait Penyediaan Perumahan oleh Pengembang Real Estate - Fennieka Kristianto (Problematika Hukum, 2018)
The enactment of Law Number 1 of 2011 concerning Housing and Settlement Areas (the Housing Act) since 2011 raises several counter-productive potentials for the housing sector in Indonesia. There are new problems related to the application of the Indonesian National Standard and it has implications for housing developers both in terms of technical and juridical aspects, which are interesting to examine in depth. What are the possibilities faced by a housing developer if the requirements for fulfilling the requirements of the Indonesian National Standard must be met by a housing developer? How is the application of Article 32 paragraph (2) and (3) of the Housing Law when faced with realities on the ground? The normative research method is used and is intended to criticize several articles in the Housing Law regarding their implications for housing provision by housing developers with the obligation to use domestic products that must meet the Indonesian National Standard (SNI).